Encountering the book of Isaiah : a historical and theological survey - Beyer, Bryan (Grand Rapids, Mich. : Baker Academic, 2007)
In this new addition to the Encountering Biblical Studies series, Bryan Beyer offers a comprehensive introduction to the book of Isaiah that surveys the book's content, its meaning in the original context in which it appeared, and its application for people today. Beyer presents the prophet's recurring themes of remnant, the sovereignty of God, the Day of the Lord, covenant obligations, Messiah, and God and the nations. He gives special attention to Isaiah's use of geographical issues to illustrate his message, Isaiah's place in the canon of Scripture, and the implications of the book for mission. Beyer has provided a clear and readable text based on his experience of teaching the Old Testament for over twenty years. As with other volumes in the series, Encountering the Book of Isaiah is specifically designed with students in mind. Chapters begin with outlines and objectives that allow easy entry into the discussion and end with conclusions and study questions that aid comprehension and recall. Informative sidebars delve further into the language, theological connections, and controversies of Isaiah. This helpful survey will be valued by any serious student of the Bible. - Publisher.
Who was Isaiah, and what do we know about him and his book? -- Isaiah's opening words to God's people : Isaiah 1:2-31 -- God's call to live in light of the future : Isaiah 2:1-5:30 -- Isaiah's call to prophetic ministry : Isaiah 6:1-13 -- The signs of Immanuel and Maher-Shalal-Hash-Baz : Isaiah 7:1-8:22 -- God's kingdom will surpass all earthly kingdoms : Isaiah 9:1-12:6 -- Oracles against the nations : Isaiah 13:1-23:18 -- The "little apocalypse" : Isaiah 24:1-27:13 -- Oracles of woe : Isaiah 28:1-33:24 -- Eschatological summation : Isaiah 34:1-35:10 -- Highlights from Hezekiah's reign : Isaiah 36:1-39:8 -- Introduction to Isaiah 40-66 -- God's people are coming home! : Isaiah 40:1-31 -- Proclamation of deliverance and restoration : Isaiah 41:1-45:25 -- The fall of Babylon : Isaiah 46:1-47:15 -- Israel's release and exaltation : Isaiah 48:1-52:12 -- The suffering servant : Isaiah 52:13-53:12 -- Celebrating the return : Isaiah 54:1-59:21 -- The grand finale of God's restoration : Isaiah 60:1-66:24 -- Isaiah and the Old Testament -- Isaiah and the New Testament -- Isaiah and the great commission.
Includes bibliographical references (pages 288-290) and indexes.
Keywords: Bible. -- Textbooks